What is open science? - Dennis, Richard; Janíček, Milan; Apel, Jochen (4EU+, 2021)
Openness and transparency are closely linked to the scientific method. But how open can and should research be? The lecture would like to invite you to participate in the current discussion about open science in its different facets by providing a broad overview - from open access over the FAIR data principles and citizen science to the European Open Science Cloud. The presentation took place on 8 November 2021 and was part of the event series "Open for you! An introduction series to open science" organized by the 4EU+ University Alliance.
Gesehen am 10.11.2021
The presentation took place on 8 November 2021 and was part of the event series "Open for you! An introduction series to open science" organized by the 4EU+ University Alliance